Short-term morbidity in transdiaphragmatic cardiophrenic lymph node resection for advanced stage gynecologic cancer - C.J. LaFargue; B.T. Sawyer; R.E. Bristow (Elsevier, 2016)
Ovarian cancer is commonly diagnosed at an advanced stage, with disease involving the upper abdomen. The finding of enlarged cardiophrenic lymph nodes (CPLNs) on pre-operative imaging often indicates the presence of malignant spread to the mediastinum. Surgical resection of CPLN through a transdiaphragmatic approach can help to achieve cytoreduction to no gross residual. A retrospective chart review was conducted on all patients who underwent transdiaphragmatic cardiophrenic lymph node resection from 8/1/11 through 2/1/15. All relevant pre-, intra-, and post-operative characteristics and findings were recorded. A brief description of the surgical technique is included for reference. Eleven patients were identified who had undergone transdiaphragmatic resection of cardiophrenic lymph nodes. Malignancy was identified in 18/21 (86%) of total lymph nodes submitted. The median number of post-operative days was 7. The overall post-operative morbidity associated with CPLN resection was low, with the most common finding being a small pleural effusion present on chest x-ray between POD# 3-5 (55%). Transdiaphragmatic CPLN resection is a feasible procedure with relatively minor short-term post-operative morbidities that can be used to achieve cytoreduction to no gross residual disease.